Best practice in critical care: anaemia in acute and critical illness. Issue 2 (25th January 2018) - Docherty, A. B.; Turgeon, A. F.; Walsh, T. S.
SUMMARY: Anaemia is common in critical illness, and standard treatment is red blood cell (RBC) transfusion, typically using a restrictive transfusion threshold of 70 g L −1 . However, there are subgroups of patients in whom it is biologically plausible that a higher transfusion threshold may be beneficial, namely, acute sepsis, traumatic brain injury and coexisting cardiovascular disease. In this review article, we will discuss the pathophysiology of anaemia, as well as its prevalence and time course. We will explore the limitations of using haemoglobin concentration as a surrogate for oxygen delivery and the concept of the critical haemoglobin concentration. We will then discuss transfusion thresholds for the general intensive care unit (ICU) population and specific subgroups.